Density Measurements in Low Pressure, Weakly Magnetized, RF Plasmas: Experimental Verification of the Sheath Expansion Effect - Zhang, Yunchao; Charles, Christine; Boswell, Roderick W. (Frontiers in Physics, 2017)
This experimental study shows the validity of Sheridan's method in determining plasma density in low pressure, weakly magnetized, RF plasmas using ion saturation current data measured by a planar Langmuir probe. The ion density derived from Sheridan's method which takes into account the sheath expansion around the negatively biased probe tip, presents a good consistency with the electron density measured by a cylindrical RF-compensated Langmuir probe using the Druyvesteyn theory. The ion density obtained from the simplified method which neglects the sheath expansion effect, overestimates the true density magnitude, e.g., by a factor of 3 to 12 for the present experiment.